Pricing Mechanisms for Energy Management in Smart Cities - Chandan, A.; Potdar, Vidyasagar; Nandi, C. (Springer International Publishing, 2018)
The power supply network, Smart Grid, is one of the most critical infrastructures which help to realize the vision of Smart Cities. Smart GridsSmart Grid can provide a reliable and quality power supply with high efficiency. However, the demand for electricity fluctuates throughout the day, and this variable demand creates power instability leading to an unreliable power supply. The inherent difficulties can be addressed to a certain extent with demand-side managementDemand-Side Management (DSM) that can play a vital role in managing the demand in Smart Grids and Microgrids, by implementing dynamic pricing using Smart Meters. This chapter reviews relevant challenges and recent developments in the area of dynamic electricity pricing by investigating the following pricing mechanismsPricing mechanisms: Time-of-Use PricingTime-of-Use Pricing, Real-Time PricingReal-Time Pricing, Critical Peak PricingCritical Peak Pricing, Day-Ahead PricingDay-Ahead Pricing, Cost Reflective PricingCost Reflective Pricing, Seasonal PricingSeasonal Pricing, and Peak Time RebatePeak Time Rebate PricingPeak Time Rebate Pricing. We also discuss four real-world case studies of different pricing mechanisms adopted in various parts of the world. This chapter concludes with suggestions for future research opportunities in this field.